Strengths and Weaknesses in Lesson Plan Designing: A Case Study on EFL Preservice Teachers’ Practicum - Vicente Jiménez, Yoana Paola (Acitya: Journal of Teaching and Education, 2025)
Lesson planning is an integral aspect in the knowledge and training of EFL teachers, providing a framework for effective classroom instruction. Consequently, this research aimed to describe EFL preservice teachers' knowledge on lesson plan designing during their practicum, identifying strengths and weaknesses. For this purpose, the qualitative method and a case study approach were employed, analyzing lesson plans, field notes, and reflective journals of four preservice teachers doing their practicum in the teacher education program at Universidad Nacional de Loja. Content analysis was used to evaluate the components of 16 lesson plans through a rubric and field notes. Findings revealed that lesson objectives were clear and aligned with Bloom's Taxonomy, although the ABCD format was not consistently implemented. Practice activities aimed to strengthen language skills but sometimes lacked diversity. Instructional materials were created to encourage participation. Assessment tasks showed high alignment with lesson objectives, and summative assessment was the type mostly used by preservice teachers. Various feedback types, including informal, positive and self-generated were identified. These insights offer valuable implications for refining preservice teacher training and enriching classroom experiences.